VPS35-Based Approach: A Potential Innovative Treatment in Parkinson's Disease - Eleuteri, Simona; Albanese, Alberto (Frontiers in Neurology, 2019)
Several symptomatic treatments for Parkinson’s disease (PD) are currently available. Still, the challenge today is to find a therapy that might reduce degeneration and slow down disease progression. The identification of pathogenic mutations in familial parkinsonism (fPD) associated to the monogenic forms of PD, provided pathophysiological insights and highlighted novel targets for therapeutic intervention. Mutations in the VPS35 gene have been associated with autosomal dominant fPD and a clinical phenotype indistinguishable from idiopathic PD. Although VPS35 mutations are relatively rare causes of PD, their study may help understanding specific cellular and molecular alterations that lead to accumulation α-synuclein in neurons of PD patients. Interacting with such mechanisms may provide innovative therapeutic approaches. We review here the evidence on the physiological role of VPS35 as a key intracellular trafficking protein controlling relevant neuronal functions. We further analyze VPS35 activity on α-synuclein degradation pathways that control the equilibrium between α-synuclein clearance and accumulation. Finally, we highlight the strategies for increasing VPS35 levels as a potential tool to treat PD.